1988
DOI: 10.1515/znb-1988-1215
|View full text |Cite
|
Sign up to set email alerts
|

Amidinatokomplexe von Bor, Aluminium, Gallium, Indium und Zinn Die Kristallstrukturen von Ph-C(NSiMe3)2AICI2 und Ph-C(NSiMe3)2SnCl3 / Amidinato Complexes of Boron, Aluminium, Gallium, Indium, and Tin The Crystal Structures of Ph-C(NSiMe3)2AlCl2 and Ph-C(NSiMe3)2SnCl3

Abstract: Abstract The trichlorides of aluminium, gallium, and indium, as well as boron tribromide and tin tetra-chloride react with N,N,N'-tris(trimethylsilyl)benzamidine to form the monomeric N.N'-bis-(trimethylsilyl)benzamidinato complexes Ph-C(NSiMe3)2MX2(M = B, Al. Ga, In; X = Cl, Br) and Ph -C(NSiMe3)2SnCl3 , respectively. All compounds have been characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…Curiously, in the same report, it was mentioned that attempts to prepare 6 resulted in the isolation of an uncharacterized yellow oil. 6 However, we found that crystalline 6 is indefinitely stable under an inert atmosphere and shows no sign of reverting to an oil, even upon gentle heating.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Curiously, in the same report, it was mentioned that attempts to prepare 6 resulted in the isolation of an uncharacterized yellow oil. 6 However, we found that crystalline 6 is indefinitely stable under an inert atmosphere and shows no sign of reverting to an oil, even upon gentle heating.…”
Section: Resultsmentioning
confidence: 64%
“…1 2 volume) under reduced pressure followed by storage at −30 • C resulted in a crop of colourless crystals which was isolated by filtration. A second crop of crystals formed upon cooling of the filtrate to −30 • C (3.9 g, 90% yield, mp 127-128 (6). Colourless crystalline 6 (mp 129-131 • C) was prepared in 84% yield from BCl 3 (10 mmol, 10 mL 1.0 M solution in CH 2 Cl 2 ) and N,N,N -tris(trimethylsilyl)benzamidine (3.4 g, 10 mmol) using the procedure described for 1.…”
Section: Preparation Of [Phc{n(sime 3 )} 2 ]Bbr 2 (1) a Solution Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the X-ray structure determinations$ are presented in Figures 1 and 2. Molecules of (3) lie on crystallographic mirror planes; key structural features include a strained four-membered chelate ring with similar B-N distances within the ring, some 16% longer than the exocyclic B-N bond distance, which is short [1.371 (8) implying N = B bonding, in contrast to only a 2.5% difference between the B-Cl distances for the two boron centres. The asymmetric unit in (5b) consists of discrete molecules.…”
mentioning
confidence: 99%
“…obtained from the reaction of L′H (L′ = {HC[(CMe)(NAr′)] 2 }, Ar′ = 2,6-Me 2 C 6 H 3 ) with equivalent amount of AlMe 3 at room temperature followed by reaction with two equivalents of I 2 in refluxing toluene afforded the aluminum diiodide L′AlI 2(40) in high yield. The L′GaCl 2(41) was prepared by the reaction of LiL′ with GaCl 3 in diethyl ether.…”
mentioning
confidence: 99%